The Impact of Common Recovery Blood Sampling Methods, in Mice (Mus Musculus), on Well-Being and Sample Quality: A Systematic Review - Alexandra L Whittaker; Timothy H Barker (Animals, 2020)
Blood sampling is often performed in laboratory mice. Sampling techniques have the potential to cause pain, distress and impact on lifetime cumulative experience. In spite of institutions commonly providing guidance to researchers on these methods, and the existence of published guidelines, no systematic evaluation of the evidence on this topic exists. A systematic search of Medline, Scopus, and Web of Science was performed, identifying 27 studies on the impact of recovery blood sample techniques on mouse welfare and sample quality. Studies were appraised for quality using the SYstematic Review Centre for Laboratory animal Experimentation (SYRCLE) risk of bias tool. In spite of an acceptable number of studies being located, few studies examined the same pairwise comparisons. Additionally, there was considerable heterogeneity in study design and outcomes, with many studies being at a high risk of bias. Consequently, results were synthesised using the Synthesis Without Meta-analysis (SWiM) reporting guidelines. Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was utilised for assessment of certainty in the evidence. Due to the heterogeneity and GRADE findings, it was concluded that there was not enough high-quality evidence to make any recommendations on the optimal method of blood sampling. Future high-quality studies, with standardised outcome measures and large sample sizes, are required.